Levo, desno, naprej ali vzvratno - Dominko Rac, Aljana (Revija inovativna pedagogika, 2025)
Critical thinking, problem-solving, and process optimization are just some of the challenges of modern society that an individual must face to successfully collaborate with modern technology. We aim to encourage teachers in the first educational triad of primary school to integrate fundamental computing and informatics knowledge into the learning process, as these are essential for learners' development. We aim to analyze teaching approaches, methods, and the effects of integrating tools into classroom instruction, considering the Framework for Computing and IT (RIN) from preschool to secondary school and the mathematics curriculum. A case study was conducted on a small, purposive sample of 1st triad pupils within the framework of a thematic activity day. The activities required pupils to solve a problem-based task through a parking lot simulation. Data was collected using qualitative methods. Data collection was based on observing pupils' work, analyzing their products, and conducting unstructured interviews. The pupils' responses were interpreted to form the study's final conclusions. The results indicate that modularity influences the process of finding solutions. Pupils who used tools to break the problem into smaller units completed the challenges more quickly. Pupils who did not use these tools reported feeling confused. The results also show that the group using modularity tools was more successful in process optimization. Based on pupil observations and interviews, perseverance, and repetition (with slight variations) are key elements in achieving the goal.
Keywords: computing and IT (RIN); Informacijsko-komunikacijska tehnologija; Osnovnošolsko izobraževanje; parking lot simulation; problem solving; računalništvo in informatika (RIN); reševanje problemov; simulacija parkirišča